Predictive Role of Hand Dimensions in Stature Estimation Among Medical Students (Journal of Rangpur Medical College, 2025)
Background: Stature or body height is one of the important and useful anthropometric parameters that determine the physical identity of an individual. The present study was undertaken to set up a standard formula to estimate stature from different hand dimensions. Objective: To find out the variations of different hand anthropometric dimensions and their relationship with stature among the students of both sexes of Rangpur Medical College. Methods: This cross-sectional, analytical study was conducted in the Department of Anatomy, Rangpur Medical College, Rangpur, from January 2018 to December 2018. 700 medical students (350 male and 350 females) were included in this study. Results: Stature had significant correlation with all hand dimensions in both male and female students. In male, highest correlation (0.995) was found for right palm length, right thumb length, left thumb length, left ring finger and lowest correlation (0.983) was found for right wrist circumference. On the other hand, in female, highest correlation was found for arm span (0.989) and lowest correlation was found for right palm length (0.968), the correlation was more prominent in male student. Conclusion: Hand dimensions can be successfully used for estimating stature. Multiplication factors are applicable to the population from which it is calculated. So, there is need to calculate multiplication factors for each parameter in every ethnic region and race.J Rang Med Col. March 2025; Vol.10, No.1: 75-81